Use decision support system to efficiently select suppliers - Yousef A. Baker, El-Ebiary; Syarilla Iryani, A. Saany; Salameh A., Mjlae (2020)
In a very competitive and fast emerging IT and wireless technology need a company to move fast and it demands the company to have the correct decision support system in choosing suppliers. The right system helps company to gain useful and meaningful data in making the right decision of selecting the right suppliers which helps them to improve their performance and sustainable in the industry that they are involve in. In making the right decision of selecting suppliers the factors of efficiency and effectiveness of the decision support system used have to be concerned. In this paper, different selection methods considering their effectiveness and efficiency systems used in choosing suppliers is discussed.